Land use mix and walking for transportation in older adults: an approach based on different metrics of the built environment - Salvador, Catharina Cavasin; Lopes, Adalberto Aparecido dos Santos; Saboya, Renato Tibiriçá de; Kanashiro, Milena; D’Orsi, Eleonora (Revista Brasileira de Gestão Urbana, 2024)
The presence of land use mix (LUM) in a neighborhood has been shown as an important aspect to promote walking as a daily means of transport. However, few studies in the area have applied different measurement strategies to test their effect on alternative modes of travel behavior, such as older adults walking. We applied six LUM measures of land use mix in two neighborhood definitions (500 and 1000m network buffers) and assessed their associations with walking for transport outcomes in adults over age 60 years from the EpiFloripa Aging study, living in the municipality of Florianópolis, Brazil, in 2013/14. Accounting for sociodemographic and environmental variables, adjusted associations found a positive relationship between four LUM and walking. The entropy index and three alternative measures defined by the intensity of commercial and nonresidential uses were positively associated with the walking for transportation, regardless of neighborhood definition. Stronger positive associations were seen when using smaller buffers and measures of the proportion of commercial uses, proportion of nonresidential uses and destination density. The results show that alternative measurements can overcome the entropy index, pointing out the need to adapt LUM measures and neighborhood scale to the geographic context and age group under analysis.